Pilihan Rasional Penari Joged Bumbung di Tabanan atas Konsekuensi Objektifikasi Tubuh - Prashanti, Devy Wira; Aditya, I Gst. Ngr. Agung Krisna; Tamim, Imron Hadi (JURNAL ILMIAH SOSIOLOGI: SOROT; Vol 5 No 1 (2025): JISSOROT, 2025)
ABSTRACT The shift in public tastes that tend to prefer erotic joged bumbung performances has received government attention with the issuance of Governor's Circular Letter Number 18 of 2024 concerning the Joged Bumbung Jaruh Traditional Dance. This study focuses on analyzing the rationality of joged dancers in Tabanan in choosing their profession. This study uses a qualitative approach method with data sources of observation, interviews, and documentation. The subjects of this study consisted of joged dancers who had received offers to perform in Tabanan district. The theoretical analysis used as a scalpel is the rational choice theory by James Samuel Coleman. The findings reveal that in carrying out their profession, there are consequences in the form of body objectification to the dancers from the pengibing, pengupah, and sekaa joged. Objectification by pengibing is carried out by touching the dancer's intimate parts by the pengibing. Objectification by pengupah can be seen from the exchange value between the dancer's body as something that can be bought with rent as wages paid. Finally, objectification by sekaa joged occurs when cooperation is established where sekaa joged plays a role in efforts to objectify the body through the accompanying gamelan. Behind that, there are three rational considerations that convince dancers to choose their profession, namely economic motivation, family support, and interest in dance. Of the three considerations, economic motivation is the biggest consideration that convinces joged bumbung dancers to choose this profession as the most rational choice. Keywords: body objectification; joged bumbung dancers; rational choice